Event-Triggered Adaptive Sliding Mode Attitude Containment Control for Microsatellite Cluster under Directed Graph. (2nd March 2021) - Guo, Fengzhi; Zhang, Shijie; Zhang, Tingting; Zhang, Anhui
Abstract : In order to investigate the attitude containment control problem for a microsatellite cluster, an event-triggered adaptive sliding mode attitude containment control algorithm is proposed for the satellite cluster flight system under directed topology, so that attitude of followers asymptotically converges to the convex hull formed by the leaders' orientations. At first, the event-triggered control strategy is introduced into the attitude containment control problem for the microsatellite cluster. The triggering condition consisting of state-dependent and time-dependent function is designed to adjust control period and avoid the Zeno behaviour. When the function value meets the triggering condition, the event is triggered, state information is sampled, control law is computed, and actuators are updated, while the control action performed in nontriggering time is the same as the previous triggering instant. Then, in the presence of model uncertainties and external disturbances, an event-triggered adaptive sliding mode attitude containment control algorithm is presented under directed topology, and sufficient and necessary conditions for the followers to enter into the target area formed by the leaders are given. Furthermore, cell partitions from graph theory are employed to investigate the influence of information topology on steady states of followers, which provides theoretical basis for orientation design of cluster satellites. Finally, simulation results show that the proposed control strategy could reduce control execution frequency, as well as ensure the similar control performance with the time-triggered one, and followers belonging to the same cell have the same steady states.